ANALISIS KEMAMPUAN PEMAHAMAN MATEMATIS SISWA KELAS VII SMP BUDI LUHUR PADA MATERI PERBANDINGAN - Zanjabila Ar-rahiiqil Mahtuum; Ani Nurhayati; Wahyu Hidayat; Euis Eti Rohaeti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
Comprehensive is one of the important mathematical abilities which is important to be mastered by the student, especially in high school. Mathematical comprehension ability become one of the basic skills that to be mastered by the student. Focus in the research is to the analyse the student  difficulties  in solve direct proportion and inverse proportion values to aspects of mathematical comprehension ability in associate something to something correctly and realize to the process.  This research used descriptive qualitative with research subject which is used 6 person. The results of this research showed that student ability in associate something to something else correctly and realize the process on the proportion material has accumulated average percentage of 78%.